STIM1: The lord of the rings?. (June 2023) - Pacheco, Jonathan; Sampieri, Alicia; Vaca, Luis
Highlights: The study by the group from Raz Palty identified a phospholipid binding domain consisting of 4 lysines (4 K). The 4 K domain is essential for positioning the SOAR domain from STIM1 near the plasma membrane and for STIM1-Orai interaction. The 4 K domain is a few amino acids away from the previously reported cholesterol binding domain (CBD) from SOAR. The fact that STIM1 possesses at least 3 lipid binding domains (two of them within SOAR) suggest that STIM1 may form specialized regions with distinct lipid compositions around the Orai channel. The composition of lipids coordinated by the STIM1 lipid binding domains may arrange around a central core formed by a single Orai channel. We have named this protein-lipid arrangement as the concentric ring hypothesis. Graphical abstract: Image, graphical abstract Abstract: STIM1 and Orai1 are the central core of the Store Operated Calcium Entry (SOCE). This calcium influx mechanism is triggered after the activation of Gq protein-coupled receptors at the plasma membrane (PM) that activate phospholipase C. The phospholipase C produces Inositol triphosphate (IP3) which rapidly diffuses throughout the cytosol, resulting in the binding and activation of IP3 receptors (IP3R) and the rapid efflux of calcium from the endoplasmic reticulum (ER) to the cytosol. The calcium depletion in the ER is sensed by the stromal interaction molecule 1 (STIM1) a single-pass transmembrane protein at the ER that binds intraluminal calcium through an EF-hand domain in its amino terminal region (Fig. 1 A). The cytosolic portion of STIM1 contains multiple domains. The region that interacts and activates Orai channels is known as SOAR (the STIM1 Orai activating region) [1] . For SOAR be accessible to Orai1, STIM1 must get an extended conformation that unlocks SOAR from its coiled-coil 1 (CC1) region [2] . The extended conformation is triggered by calcium depletion at the ER that oligomerizes STIM1. The oligomers of STIM1 then translocate to a close distance between two opposing membranes, forming what is known as ER-PM junctions. STIM1 accumulates at ER-PM junctions conforming the denominated STIM1 puncta.